Synthesis of 4-Hydroxy-2-Methylchalcone from meta-Cresol Formilation Product and Its Activities as an Antibacteria - Ismiyarto Ismiyarto; Suyanti Suyanti; Ngadiwiyana Ngadiwiyana; Purbowatiningrum Ria Sarjono; Nor Basid Adiwibawa Prasetya (Jurnal Kimia Sains dan Aplikasi, 2018)
Research on the synthesis of 4-hydroxy-2-methylchalcone from 4-hidroksi-2-metilbenzaldehida as formilated meta-cresol product and its antibacterial activity test has been conducted. As the first step, synthesis of 4-hydroxy-2-methylbenzaldehyde was carried out by treatment meta-cresol with chloroform through the Reimer-Tiemann formylation. Product is a brown solid with 23.94% yields. Furthermore, the 4-hydroxy-2-methylchalcone was synthesized using the 4-hydroxy-2-methylbenzaldehyde and acetophenone through the Claisen-Schmidt reaction. The product is a brownish yellow solid with 29.74% yields. Antibacterial test against Escherichia coli and Staphylococcus aureus bacteria was carried out by comparing the activity of 4-hydroxy-2-methylchalcone with 4-hydroxy-3-methoxychalcone, and chalcone compounds. The antibacterial activity test showed that the 4-hydroxy-2-methylchalcone compound, 4-hydroxy-3-methoxychalcone, and chalcone compounds gave a better antibacterial activity against Escherichia coli than the Staphylococcus aureus.